Conductive grid patterns prepared by microcontact printing silver nanoparticles ink. (30th January 2017) - Xin, Zhiqing; Liu, Yu; Li, Xiu; Liu, Shili; Fang, Yi; Deng, Yongqiang; Bao, Chao; Li, Luhai
Abstract: Metal grid transparent conductive electrodes have been developed by traditional printing techniques, but lower resolution of grid line has limited its performance. In this study, conductive grid patterns with ~10 µ m width were created on the polyethylene terephthalate (PET) substrate by microcontact printing ( µ CP) silver nanoparticles ink. We have found that the composition of silver nanoparticles ink and the O2 plasma treated time of polydimethylsiloxane (PDMS) stamp were critical for the µ CP process. Specially, the hole size of stamp has great influence on the patterns shape when using grid-structured stamp. This is because the break of liquid bridge formed between two adjacent lines of stamp depends on the hole size of stamp during the dry process of ink. Larger hole was beneficial for the formation of grid patterns with smooth edge. Conductive grid patterns with typical sheet resistance of 610 Ω/□ and 74% transparency were acquired over the entire 1 cm square area using 40 µ m hole stamp. This method will lead to a facile strategy to prepare conductive electrode.